Metal–organic frameworks based on halogen-bridged dinuclear-Cu-nodes as promising materials for high performance supercapacitor electrodes. Issue 47 (21st November 2017) - Xiong, Xin; Zhou, Liuyin; Cao, Wenjie; Liang, Jiyuan; Wang, Yazhen; Hu, Siqian; Yu, Fan; Li, Bao
Abstract : Two halogen-bridged di-nuclear Cu-based 3D porous frameworks present high specific capacitance and good cycling stability. Abstract : Two halogen-bridged di-nuclear Cu-based 3D porous metal–organic frameworks (MOFs), {[Cu2 Cl(OH)(L)2 ]·(CH3 OH)4 } n (1 ) and {[Cu2 Br(OH)(L)2 ]·(CH3 OH)4 } n (2 ), have been obtained via solvothermal methods with the bi-functional ligand (HL = 4, 2′:6′, 4′′-terpyridine-4′-carboxylic acid). These Cu-based frameworks exhibit similar two-interpenetrating frameworks, and 1D channels were left in the packing structures. These MOF materials were then applied as electrode active materials in supercapacitors. Compound1 presents a high specific capacitance and good cycling stability in 6 M KOH electrolyte compared to2 . The maximum specific capacitance of electrode1 could reach 1148 F g −1 at a current density of 0.5 A g −1, along with a high capacitance of 90% retained after 2000 cycles at a current density of 10 A g −1 in a 6 M KOH solution. The successful introduction of halogen and hydroxyl ions into the final structures might be responsible for the high performance of the supercapacitor, which makes these Cu MOFs a candidate for an electrode active material for electrochemical energy storage.